Consolidating diverse modeling methods and spatial prioritization for multispecies connectivity planning - Bohnett, Eve; Oetting, Jon; Noss, Reed; O’Brien, Michael; Frakes, Robert; Smith, Dan; Lockhart, Sarah; Mullinax, Jennifer; Poor, Erin E.; Scheick, Brian; Hoctor, Thomas (Frontiers in Conservation Science, 2024)
Given the different life histories and movement behaviors of diverse species, how to reconcile conservation measures to benefit all species is a critical concern for landscape conservation planning. Understanding land cover composition and finding multispecies movement routes across heterogeneous landscapes are crucial to maintaining many target species. The primary objectives of this study were to determine the optimal environment in Florida that promotes multispecies connectivity in landscapes increasingly threatened by rapid suburban development and to enhance methods for delineating the state's ecological networks. Potential functional connectivity of the focal species that have statewide distributions and are considered priorities because of the historical and current threats to their population viability, Florida black bear (Ursus americanus floridanus), Florida panther (Puma concolor coryi), eastern indigo snake (Drymarchon couperi) and southern fox squirrel (Sciurus niger niger) were modeled using Linkage Mapper, Omniscape, and resistant kernels. We also combined the quantiles from each method for a single species combination approach to leverage the results from the three models for planning purposes, and finally we integrated the results into a novel multiple species, multimodel connectivity mapping approach. Following the corridor analysis, a comparison was made between multispecies connectivity maps, the current managed conservation lands, and the main priority areas for the Florida Wildlife Corridor, a previously developed planning network of natural hubs and corridors. Our goal was to identify priority areas for all four species, with a particular focus on areas that are not protected. Finally, we used the spatial prioritization software Zonation to identify areas of conservation priority, while also illustrating the impacts of infrastructure (built infrastructure, roadways, mining, and future development 2040 and 2070 projections) and threats from human activity (landscape fragmentation, recreation, pollution, contamination, and clean-up sites). Species-relevant connectivity models that incorporate a group of focal species with both complementary and opposing habitat requirements can better inform biodiversity conservation and landscape design decisions for multiple species, and better cover a wider range of other species of conservation interest.